Answer:
-4
-10x+6
Step-by-step explanation:
I am going to assume the (Something)x2 means (Something)
. Then, the expression is 2
-6
+4x-6x+9-3=-4
-10x+6
Answer:
D. 2 3 • 3 2 • 5
Step-by-step explanation:
ig I need at least 20 characters to submit my answer. :)
Answer:
Denote adding term = a
a = (5/6x) - 4 - (1/2x) - 4
a = (5/6x) - (1/2x)
a = (5/6x) - (3/6x)
a = (2/6x)
a = (1/3x)
*******************************
a = (5/6)x - 4 - (1/2)x - 4
a = (5/6)x - (1/2)x
a = (5/6 - 1/2)x
a = (1/3)x
Hope this helps!
No cap absolutely I think its the 2nd one tho
Answer:
See below
Step-by-step explanation:
According to triangle mid-segment theorem:
c) CT = 1/2 EN
Given that EN = 43
=> CT = 1/2 (43)
=> CT = 21.5
a) AE = 2PT
Since PT = 13
=> AE = 2(13)
=> AE = 26
b) AN = 2CP
Given that CP = 29
=> AN = 2(29)
=> AN = 58
d) Perimeter of AEN = AE + EN + AN
P = 26 + 43 + 58
P = 127
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
Hope this helped!
<h3>~AH1807</h3>